'Gendering illiterature: the representation of the Egyptian women left behind in Ayman Zohry's "The Mediterranean Sea"'. Issue 1 (2nd January 2022) - Kebsi, Jyhene
ABSTRACT: This paper shifts the focus from male paperless migrants to the women who stay in their country of origin. My analysis of the discrepancy between borderless economics and the bordered movement of people explores the representation of the women left behind in Ayman Zohry's novella 'The Mediterranean Sea', which describes irregular migration from Egypt to Italy. This paper investigates the intersection between the forces of patriarchy and globalisation in the lives of the women who are left in the sending countries. The article starts by shedding light on the writer, who is an expert in immigration studies. The second section of this essay focuses on the wives' struggle against the glocal masculine and geopolitical dictates. The third part of the paper analyses the juncture of gender and global capital in the lives of the mothers left behind. My investigation of the hardships endured by migrants' wives and mothers demonstrates that immigration torments those women who stay in the homeland as much as it afflicts the spouses who travel to 'Hopeland' (Obi, Cyril. 2007. "From Homeland to Hopeland? Economic Globalization and Ogoni Migration in the 1990s." In The Cultures of Economic Migration: International Perspectives, edited by Suman Gupta, and Tope Omonyi, 115. Burlington, VT: Ashgate). My main argument is that the Egyptian women left behind have to strive against both the contradictions induced by globalisation and the subordination generated by male domination.